Impact of lecture delivery by using PowerPoint presentation and black board and chalk in second year MBBS students in Pharmacology - Jose, Preetha; Thaha, Firoz; Varghese, Kavitha; Poomali, Aruvi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The use of electronic media and audio-visual aids for teaching has become increasingly common in medical colleges. This teaching method is considered superior to blackboard and chalk by majority of the students and teachers. But the quality of medical education has not drastically improved in comparison. This study compares the impact of lecture delivery using PowerPoint presentation as opposed to blackboard and chalk in medical students attending pharmacology classes. Methods: This was a cross sectional study done in the second year MBBS students attending pharmacology classes in the Department of Pharmacology at Government Medical College, Thrissur in the year 2017. Students were given lectures on two similar topics, one using PowerPoint presentation and the other using blackboard and chalk by the same teacher. The students were given a post-test after each lecture and marks were analysed using Independent student’s t test. A feedback was also taken from the students regarding the two lecture delivery methods and the data is expressed in percentages. Results: This study was done in 149 medical students who attended pharmacology classes. The students scored significantly higher marks in the post-test when the lecture was taken using black board and chalk (p <0.001). 58% of the students preferred lecture delivery using PowerPoint compared to 38% preferring black board and chalk. 4% of the students considered both methods equally good. Conclusions: Lecture delivery using black board and chalk was found to be more efficacious than power point presentation when the marks of the post-tests were compared. However, majority of the students preferred lecture delivery using power point to blackboard and chalk.